Editorial - Martins, Lauber (Revista de Engenharia Térmica, 2023)
The editorial of Thermal Engineering of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. The naval sector dominates global commerce totalizing more than 80% of volumes transported]. Heavy fuel oil and marine gas oil are the most utilized fuels and make up 2 to 3% of the human produced CO2 dumped in the atmosphere. Until the year 2050, the International Maritime Organization (IMO) is committed to a 50% reduction of ship greenhouse gases (GHG) emissions with predicted full elimination by 2100. However, military ships are expected to require ten times more electric power than current navy vessels. As a result, the all-electric military ship initiative depends heavily on scientific research and development of environmentally benign high density power generation systems. In that scenario, fuel cells bring a possible path to problem solution. The low-temperature Polymer Electrolyte Membrane Fuel Cell (PEMFC) is recognized to be the most popular FC. Although PEMFC has been used in transportation (e.g., vehicular, ships), PEMFC general use still brings several concerns, due to some shortcomings (e.g., water management, platinum content, Nafion membrane high cost, free energy demanding H2 availability). In parallel, there has been a demand to develop innovative and environmentally correct technologies for alternative energy sources to replace traditional fossil and nuclear sources, including the naval sector, for quite a while, and this need is current, and the main hurdles to overcome are the generation and storage of renewable energy in a technically and economically viable way. The mission of Thermal Engineering is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.